2011
DOI: 10.1037/a0025015
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the reciprocal relationships between parental physical aggression and children's externalizing problem behavior in China.

Abstract: The study examines gender differences in the reciprocal relations between parental physical aggression and child externalizing problem behavior in China. Four hundred fifty-four Chinese elementary school-age children reported on three forms of their parents' physical aggression toward them (i.e., mild corporal punishment, severe corporal punishment, and physical abuse) and their externalizing problem behavior at two time points, 6 months apart. Structural equation modeling revealed that the three types of pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 45 publications
6
67
1
Order By: Relevance
“…Parents' self-report of discipline strategies were measured using the Chinese version of the ParentChild Conflict Tactics Scales (CTSPC; Leung, Wong, Chen, & Tang, 2008;Straus et al, 1998), a widely used noninvasive measure with established reliability and validity (Leung et al, 2008;Wang & Liu, 2014;Xing et al, 2011). The CTSPC is composed of five subscales: nonviolent discipline (4 items), psychological aggression (5 items), corporal punishment (6 items), physical maltreatment (3 items), and extreme physical maltreatment (4 items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents' self-report of discipline strategies were measured using the Chinese version of the ParentChild Conflict Tactics Scales (CTSPC; Leung, Wong, Chen, & Tang, 2008;Straus et al, 1998), a widely used noninvasive measure with established reliability and validity (Leung et al, 2008;Wang & Liu, 2014;Xing et al, 2011). The CTSPC is composed of five subscales: nonviolent discipline (4 items), psychological aggression (5 items), corporal punishment (6 items), physical maltreatment (3 items), and extreme physical maltreatment (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…In childhood, psychological aggression and corporal punishment were the most common forms of parental harsh discipline (Straus, Hamby, Finkelhor, Moore, & Runyan, 1998;Wang & Liu, 2014). Many studies have found that parental use of harsh discipline is positively related to a number of negative developmental outcomes (e.g., aggression, delinquency, anxiety, and depression) in children (Miller-Perrin, Perrin, & Kocur, 2009;Xing & Wang, 2012;Xing, Wang, Zhang, He, & Zhang, 2011). To prevent and intervene on parental harsh discipline, researchers have tried to identify the causes of parental harsh discipline.…”
Section: Introductionmentioning
confidence: 98%
“…Despite numerous studies have demonstrated that children exposed to parental harsh discipline (e.g., psychological aggression, corporal punishment, and physical abuse) are at risk for a number of negative developmental outcomes, including aggression, anxiety, and depression (i.e., Fine et al, 2004; Xing et al, 2011; Xing and Wang, 2013), harsh discipline is still the prevalent parental disciplinary technique in modern Chinese families. According to a large sample survey conducted in Mainland China (Wang and Liu, 2014), more than 80% of parents with children aged 3–6 reported the use of psychological aggression, and about 70% of parents reported the use of corporal punishment during the previous year.…”
Section: Introductionmentioning
confidence: 99%
“…Poor parenting behavior, in turn, has negative effects on children's behavior (Vissing, Straus, Gelles, & Harrop, 1991;Miller-Perrin, Perrin, & Kocur, 2009;Xing & Wang, 2013;Xing, Wang, Zhang, He, & Zhang, 2011). Based on these two theoretical models and previous empirical research, Deater-Deckard (1998) offered hypotheses about the relationships between parenting stress, parenting behavior, and child adjust ment.…”
mentioning
confidence: 97%